Dobra i prawa osobiste po śmierci twórcy (na podstawie kodeksu cywilnego, prawa autorskiego i prawa własności przemysłowej) - Czub, Krzysztof (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
This article raises the question of personal interests and moral rights after the death of the author, presented on the basis of widely grasped civil law. The death of the author crowned (sets) finally the intangible asset (work, invention, industrial design, trademark etc.) and any relationship between the author and the outcome of his/her creativity. No personal interest can survive the creator, which does not exclude the protection of the values associated with the author or his/her work post mortem auctoris. There are, however, formally considering, the other ‘transformed’ assets – even if, as in the copyright regime, they were in the content or structure formed in the likeness of their prototypes. These assets are subject of the own rights of other entities (persons close to the creator, social organizations), and last as long as the creation of human intellect is the subject of legal transactions
Keywords: moral rights; personal interests; authorship; intellectual property; IP rights; post-mortem rights